Between hope and a hard place: Boys and young men negotiating gender, poverty and social worth in Ethiopia - Crivello, G; van der Gaag, N (Young Lives, 2016)
The second decade of life is increasingly recognised as a crucial phase and a ‘window of opportunity’ for policy intervention. It is a period of social transition as young people navigate complex life choices around schooling, work, and intimate and family relationships. In recent years, adolescence has risen high on the global agenda, but boys are often marginalised by an overwhelming focus on girls and on female adolescence, which also means that a gendered perspective is missing. Although boys and young men hold more powerful positions in society than girls and young women, their needs may be disadvantaged by sexual stereotypes, social norms and economic adversity. In this paper, we use longitudinal qualitative and survey data from Young Lives, an ongoing study of childhood poverty in Ethiopia, to trace the diverging trajectories of a group of adolescent boys across their second decade of life (aged 12 to 20), from a relational gender approach that also looks at girls’ experiences. The paper is particularly interested in the way poverty and gender interact in boys’ and girls’ lives to shape their pathways to adulthood, including their aspirations, agency, actions, and changing roles and responsibilities in their intimate, family and community contexts. We describe the obstacles boys and young men face as they grow into adults, the diverse strategies they employ to overcome them, and how these differ from girls’ and young women’s experiences. We examine multiple factors affecting boys’ trajectories of hope across time, and find that, as they grow older, the failure to find work is particularly crushing of hope, and undermines their efforts to progress in life. The metaphor of being stuck ‘between hope and a hard place’ draws attention to the real-life struggles of boys and young men to remain hopeful, connected and productive with very few resources to draw upon. The paper concludes by drawing out the policy implications. It calls for stronger gendered evidence on the relationship between gender inequality and childhood poverty, and an approach to gender justice that include boys and young men, as well as girls and young women.